Medical and economic impacts of managing corneas from older donors at the tissue bank—a single-center retrospective study spanning over 12 years - Hatzfeld, Anne-Sophie; Germain, Nicolas; Maboudou, Patrice; Dhayer, Mélanie; Marchetti, Philippe (Frontiers in Medicine, 2024)
Aim To evaluate the impact of corneas from donors over 80 years of age on the activity of the North of France Tissue Bank and to determine the potential cost implications for banks using corneas from older donors. Methods We analyzed data from a single-center retrospective cohort study of 6,023 corneas preserved at the Lille Tissue Bank between 2012 and 2023. Donors, unrestricted by age, were divided into two groups: younger (≤ 80 years) and older (> 80 years). Corneas were categorized based on endothelial cell density (ECD). Data were collected from patients who underwent corneal transplantation. A financial impact model was created to assess the effects of using corneas from different age groups on the overall benefits of corneal transplant procedures. Results The average donor age was 67.5 ± 14.5 years. The median age of donors gradually increased from 66 to 73 years over the 12-year study period, with donors over 80 years old representing more than 24% since 2021. Corneas from older donors had a higher discard rate (62.53% vs. 39.66%) due to poor endothelial quality and serological concerns (both p < 0.0001). Additionally, these corneas had lower ECD, with a larger proportion deemed unsuitable for grafting due to low ECD (30% vs. 8.2%). Corneas from younger donors were more often used for endothelial transplants, which require higher ECD. The mean economic benefit per cornea showed a moderate negative correlation with donor age. The net benefit of corneal transplants decreased as the proportion of donors aged over 80 years increased. It is predicted that a net benefit of zero would be attained when the proportion of donors over 80 years is 44.4%. Conclusion Using corneas from donors over 80 years of age can help alleviate the shortage of donor tissue and be effective if certain quality standards are met. However, additional costs incurred by eye banks must be factored into this equation.